US Aid and gender equality: social movement vs civil society models of funding. Issue 4 (19th May 2018) - Irvine, Jill A.
ABSTRACT: Despite the fact that the assumed link between women's empowerment, peace, and democratization has taken a firm hold in both theory and practice, the effectiveness of funding empowerment remains highly contested in the literature on gender, war, and democratic transformations. Drawing upon over a decade of fieldwork, this article offers lessons from the Balkans for funding women's empowerment, with a particular focus on postconflict political transitions. I argue that there are two fundamentally different approaches to funding women's empowerment, what I call the civil society model and the social movement model, and I lay out theoretical reasons why the social movement model is more likely to achieve enduring political change. I then provide a case study of how the United States government promoted elements of the social movement model in Croatia and Serbia as part of its democratization assistance, focusing on the challenges and promise of this approach.